2011
DOI: 10.1074/jbc.m110.178798
|View full text |Cite
|
Sign up to set email alerts
|

Toll-like Receptor 3 (TLR3) Induces Apoptosis via Death Receptors and Mitochondria by Up-regulating the Transactivating p63 Isoform α (TAP63α)

Abstract: Toll-like receptor 3 (TLR3), a member of the pathogen recognition receptors, is widely expressed in various cells and has been shown to activate immune signaling pathways by recognizing viral double-stranded RNA. Recently, it was reported that the activation of TLR3 induced apoptosis in some cells, but the detailed molecular mechanism is not fully understood. In this study, we found that in endothelial cells polyinosinic-polycytidylic acid (poly(I-C)) induced dose-and time-dependent cell apoptosis, which was e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
75
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 101 publications
(79 citation statements)
references
References 42 publications
3
75
1
Order By: Relevance
“…Juxtaposition of ER and mitochondria promotes interorganelle crosstalk and mediates cell death, which is tightly controlled by the Bcl-2 family proteins [14,15]. The latter regulate either caspase 8-mediated extrinsic pathway or caspase 9/mitochondria-mediated intrinsic pathway, both being used in TLR3 mediated apoptosis [16,17]. Among the three subgroups of the Bcl-2 family proteins, we found poly(I:C) significantly and preferentially up-regulated BH3-only molecules including BAD, Noxa and tBid in SK-N-AS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Juxtaposition of ER and mitochondria promotes interorganelle crosstalk and mediates cell death, which is tightly controlled by the Bcl-2 family proteins [14,15]. The latter regulate either caspase 8-mediated extrinsic pathway or caspase 9/mitochondria-mediated intrinsic pathway, both being used in TLR3 mediated apoptosis [16,17]. Among the three subgroups of the Bcl-2 family proteins, we found poly(I:C) significantly and preferentially up-regulated BH3-only molecules including BAD, Noxa and tBid in SK-N-AS.…”
Section: Discussionmentioning
confidence: 99%
“…Juxtaposition of ER and mitochondria promotes inter-organelle crosstalk and mediates cell death. The apoptotic crosstalk between the two organelles is tightly controlled by the Bcl-2 family proteins [14,15], which then regulate either caspase 8-mediated extrinsic pathway or caspase 9/mitochondria-mediated intrinsic pathway, both being used in TLR3 mediated apoptosis [16,17]. Increased production of reactive oxygen species and modulation of cell death by anti-oxidant manganese superoxide dismutase (MnSOD) and/or copper-zinc SOD (CuZnSOD) may be linked to these sequential events [18,19].…”
Section: Introductionmentioning
confidence: 98%
“…Other studies have suggested that an excessive amount of poly(I:C) may produce a response spectrum unsuitable for viral clearance, such as transactivating p63 (Tap63␣)-dependent apoptosis (27), activation of intracellular negative regulatory molecules, including A20, tumor necrosis factor-related apoptosis-inducing ligand receptor (TRAIL-R), and ubiquitin 1 (28); and type I IFN-dependent exhaustion of memory T cells (29,30) and dendritic cells (DCs) (31). However, the underlying mechanisms remain to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown through multiple studies that TLRs can activate apoptotic cascades. TLR3 can activate apoptosis through both the intrinsic and extrinsic pathways through the binding of the respective synthetic ligand polyinosinic:polycytidylic acid [poly(I:C)] in endothelial cells [24]. TLR2 can activate apoptosis through MyD88 which in turn activates the Fas-associated death domain-caspase-8 pathway in monocytes/macrophages through direct death-domain interactions [25,26,27].…”
Section: Toll-like Receptor Signaling: Role In Innate Immune Responsementioning
confidence: 99%